Waste Analysis of the International Delivery Service Process Using Lean Six Sigma in Logistics Service Provider Companies - Ega Rizkiyah; Hari Supriyanto; Kumara Pinasthika Dharaka; Lestary Grace; Ivana Rahmaningtyas (Journal of Applied Engineering and Technological Science (JAETS), 2024)
International shipping poses challenges such as customs clearance delays, slow delivery speeds, and process bottlenecks, leading to time wasstage, increased costs, and potential profit losses. These issues impact specific processes and customer satisfaction. Lean Six Sigma offers a robust framework for identifying and eliminating waste in international shipping processes. Applying the lean service approach, we identified four key waste types in international shipping: delay, duplication, unnecessary movement, and error. However, a Pareto diagram highlighted delay and error as critical culprits, with sigma values of 1.85 for delay and 2.92, 3.46, 3.77 for the three error types, respectively. These low sigma values indicate significant room for improvement After conducting an impact analysis and failure mode analysis (FMEA), four improvement recommendations were proposed: the implementation of an online shipping form filling system, providing customs training to all counter employees, and creating SOPs for inspection processes at the warehouse. These recommendations form a roadmap for international shipping companies to embrace Lean Six Sigma, enhancing efficiency, reducing costs, and improving customer satisfaction.